Penegakan Hukum Pidana terhadap Penanganan Gelandangan dan Pengemis di Tempat Umum: (Studi Komparatif KUHP Lama dan Baru Berdasarkan Putusan PN Kab. Semarang No.145/Pid.C/PN UNR ) - Gunawan Widjaja; Songga Aurora Abadi; Alam Anbari (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The phenomenon of homelessness and begging in public places remains a complex social problem that impacts public order and legal norms. The main problem in this study is how criminal law is applied to homelessness and begging in public places, and how the provisions compare in the old Criminal Code and the new Criminal Code based on Law Number 1 of 2023. This study uses a normative juridical method with a legislative approach and literature study. In the old Criminal Code, begging is regulated in Article 504, which threatens imprisonment for anyone who begs in public. Meanwhile, the new Criminal Code regulates similar acts in Article 425, which no longer uses the term